ANALISIS PERBANDINGAN KINERJA KEUANGAN PEMERINTAH BOJONEGORO DAN JOMBANG TAHUN 2010-2014 - JAENURI, . (Jurnal Ekonomi Pembangunan, 2016)
The research is aimed to find out about financial performance between Bojonegoro Regency and Jombang Regency Government in year 2010-2014. The research is done in Bojonegoro Regency and Jombang Regency, data used is collected by documentation on Regional Expenditure and Income Budget (APBD) of Bojonegoro Regency and Jombang Regency. Analysis technique used in this research is descriptive quantitative.Analysis shows that financial performance in Bojonegoro regency is better than Jombang regency. It can be seen from: 1. Average financial independency ratio. 2. Average of Regional Original Income Effectivity Ratio. 3. Average of activity ratio (harmony) of Operation Cost and Capital Cost. 4. Average of growth ratioÂ